Efektivitas Aplikasi Tiktok sebagai Pelestari Tradisi Siraman dalam Pernikahan Adat Jawa di AKSARA Wedding Organizer - Refa Widia Pratiwi (Yumary: Jurnal Pengabdian kepada Masyarakat, 2023)
Purpose: The purpose of this study aims to evaluate the effectiveness of using TikTok in an effort to preserve the traditional Javanese wedding splash tradition by AKSARA Wedding Organizer . Methodology: This study used a qualitative method with data collection techniques in the form of in-depth interviews, observations, and documentation. The in-depth interviews were conducted with the management and staff of Aksara Wedding Organizer, as well as with couples who had used the TikTok application to preserve and disseminate the siraman tradition in their wedding. The observations were conducted during siraman ceremonies that used the TikTok application as a medium for preservation and dissemination. The documentation was collected in the form of TikTok videos of siraman ceremonies, as well as photos and videos from the Aksara Wedding Organizer archive. Results: The results of this study will provide insight into how far TikTok is effective in promoting and preserving the traditional Javanese wedding ceremony tradition and can serve as a guideline for AKSARA Wedding Organizers in using this social media platform for cultural preservation activities in the future. Conclusion: The results of this study suggest that the TikTok application can effectively preserve the Siraman tradition in Javanese traditional weddings. The participants who engaged with the application showed a significant increase in their knowledge and interest in the Siraman tradition. Aksara Wedding Organizer can use these findings to continue promoting and preserving traditional practices through digital platforms.